Psychopathy and Ratings of Persuasiveness: Examining Their Relations in Weaker and Stronger Contexts. (November 2018) - Weiss, Brandon M.; Lynam, Donald R.; Miller, Joshua D.
Previous work has demonstrated mostly null to small associations between boldness and externalizing behaviors associated with psychopathy. The present study replicated this finding and examined an alternate manner in which boldness may be relevant to the construct of psychopathy, namely by enhancing psychopathic individuals' capacity for interpersonal manipulation. Using data collected from a Mechanical Turk sample, we measured persuasiveness using ratings of video-recorded product pitches and examined the relations between psychopathic and general traits and persuasiveness across weaker (improvised) and stronger (scripted) conditions. Boldness exhibited a small, positive relation with perceived persuasiveness in the improvised condition only; conversely, psychopathic traits related to antagonism/meanness and disinhibition exhibited small negative associations with persuasiveness and trust in the scripted condition. The results suggest that boldness may help individuals persuade others so as to achieve desired outcomes, although the effect was quite small in nature, whereas psychopathic individuals who are not high on boldness may need to use other tactics (e.g., intimidation, coercion) to manipulate others.